Uma nova abordagem para o estudo do planejamento e controle da produção (PCP): a ótica da Teoria da Complexidade - Dutra, Fernando Augusto Ferreira; Erdmann, Rolf Hermann (Revista Gestão da Produção Operações e Sistemas, 2006)
Nowadays, one of the main organizational challenges is to adapt to an environment that changes faster than the organizations can follow. Such organizations are still attached to the mechanistic model. This work originated from the idea that the organizational systems no more behave in a linear way. It is suggested here a new approach, under the view of the Complexity Theory, in order to study and analyze the Production Planning and Control (PPC) system of the organizations. The Complexity Theory suggests that the systems should be observed as Complex Adaptive Systems (CAS). These types of systems have as a basic property the ability to adjust their behavior in order to deal with new situations in their environment. It is believed that the observation of the PPC as a CAS can contribute for the organizations in a way that they can obtain significant insights in order to manage their operations. Keywords: Operation Management; PPC; Complexity Theory.